Photafish system: An affordable device for fish photography in the wild - García-Melo, Jorge E.; García-Melo, Luís J.; García-Melo, Jesús D.; Rojas-Briñez, Diana K.; Guevara, Giovany; Maldonado-Ocampo, Javier A. (Zootaxa, 2019)
This paper describes the Photafish System, an innovative technique for capturing high-quality digital images of live freshwater fishes and other aquatic organisms in the field. This system may improve and facilitate the visual documentation of such organisms to illustrate guidebooks, populate online databases and support scientific papers, particularly taxonomic ones. The system was designed and tested to produce Taxonomically Informative Photos (TIPs) of living specimens and employs an Aquarium Assembly for Photography (AAP) distinguished by its portability and low cost. Using Neotropical freshwater fishes as a model, we propose an optimized protocol for documenting the morphology of live specimens to support taxonomy, as well as awareness and conservation of freshwater biodiversity. This paper addresses the technical aspects and challenges of field studio photography in remote locations. Tricks gleaned from personal experiences with nature photography are also shared. Finally, we briefly discuss the advantages and weaknesses of our approach.